IMPLEMENTATION OF HUMAN RESOURCE MANAGEMENT IN IMPROVING THE QUALITY OF LECTURERS AT MUHAMMADIYAH PARE-PARE UNIVERSITY - Nur, Amiruddin Z.; Ondeng, M. Syarifuddin; Abubakar, Achmad; Siraj, Arifuddin (Program Pascasarjana, UIN Alauddin Makassar, 2022)
This paper talks about how implementing human resource management improves the quality of lecturers at the University of Muhammadiyah Parepare. The research method used is descriptive research that is analyzed qualitatively. Data sources are obtained from leaders, bureau heads, deans, lecturers, and documentation. The results showed that: 1) the system and process of implementing human resources related to lecturers, carried out professionally and under applicable regulations and regulations; 2) the quality of lecturers in terms of distribution based on faculties and study programs has not been evenly distributed; 3) efforts to improve the quality of lecturers carried out include further study studies, integrated learning, research, scientific forums, scientific publications, communication forums, mastery of information technology programs, parent programs or internships, and other supporting activities; 4) supporting and inhibiting factors for improving the quality of lecturers in general, including leadership, individual motivation, limited budgeting, and lecturer welfare.